Clinical characteristics of immunoglobulin G4–related disease: a prospective study of 118 Chinese patients - Lin, Wei; Lu, Sha; Chen, Hua; Wu, Qingjun; Fei, Yunyun; Li, Mengtao; Zhang, Xuan; Tian, Xinping; Zheng, Wenjie; Leng, Xiaomei; Xu, Dong; Wang, Qian; et al. (Rheumatology (Oxford, England), 2015)
To characterize the clinical features of IgG4-related disease (IgG4-RD) in China. A prospective cohort study of IgG4-RD was carried out in Peking Union Medical College Hospital between 2011 and 2013. Patients with newly diagnosed IgG4-RD were enrolled. A total of 118 patients with IgG4-RD were enrolled, including 82 males and 36 females, aged 53.1 (s.d. 13.6) years. The most common symptom at onset was lacrimal gland swelling (38/32.2%). A range of organs were involved: 77 patients (65.3%) had lymphadenopathy, 76 (64.4%) had sialadenitis, 60 (50.8%) had dacryoadenitis, 45 (38.1%) had autoimmune pancreatitis, 32 (27.1%) had pulmonary involvement, 31 (26.3%) had periaortitis/retroperitoneal fibrosis, 29 (35.4% of male patients) had prostatitis and 29 (24.6%) had renal involvement. In addition, there were 21 (17.8%) cases of sclerosing cholangitis, 15 (12.7%) of sinusitis and 10 (8.5%) of inflammatory pseudotumour. Uncommon manifestations included mediastinal fibrosis, skin involvement, sclerosing thyroiditis, hypophysitis, orchitis and colitis. Multiple organ involvement was observed in 93 patients, whereas only 4.2% had only a single organ involved. A history of allergy was reported in 73 (61.9%) patients. The serum IgG4 level was elevated in 97.5% and was correlated with the number of organs involved. Most patients were treated with glucocorticoids alone or in combination with immunosuppressive drugs, and the majority usually improved within 3 months. IgG4-RD is a systemic inflammatory and sclerosing disease. Parotid and lacrimal involvement (formerly called Mikulicz's disease), lymphadenopathy and pancreatitis are the most common manifestations. Patients with IgG4-RD showed favourable responses to treatment with glucocorticoids and immunosuppressive agents.